Hollywood at the races : film's love affair with the turf - Shuback, Alan (University Press of Kentucky, 2019)
Horse racing was so popular and influential between 1930 and 1960 that nearly 150 racing themed films were released, including A Day at the Races, Thoroughbreds Don't Cry, and National Velvet. This fast-paced, gossipy history explores the relationship between the Hollywood film industry, the horse racing industry, and the extraordinary participation of producers, directors, and actors in the Sport of Kings. Alan Shuback details how all three of Southern California's major racetracks were founded by Hollywood luminaries: Hal Roach was cofounder of Santa Anita Park, Bing Crosby founded Del Mar with help from Pat O'Brien, and Jack and Harry Warner founded Hollywood Park with help from dozens of people in the film community. The races also provided a social and sporting outlet for the film community -- studios encouraged film stars to spend a day at the races, especially when a new film was being released. The stars' presence at the track generated a bevy of attention from eager photographers and movie columnists, as well as free publicity for their new films. Moreover, Louis B. Mayer, Bing Crosby, Fred Astaire, Betty Grable, and Don Ameche were all major Thoroughbred owners, while Mickey Rooney, Chico Marx, and John Huston were notorious for their unsuccessful forays to the betting windows.